Evaluation of absolute volume of human fetal kidney's cortex and medulla during gestation - Vlajković Slobodan; Daković-Bjelaković Marija; Čukuranović Rade; Popović Jasmina (Vojnosanitetski Pregled)
Background. Human fetal kidney is quite different from the mature kidney, both macroscopically and hystologically. Lobulated surface of the human fetal kidney reflects its inner organization. Aim. To determine the fetal kidneys' volume according to the gestational age, to establish periods of their maximal and minimal growth and to compare these values for various gestational ages. Methods. Forty five human fetal kidneys aged from IV to X lunar months were analyzed. Kidneys were divided into nine groups according to their gestational age. The volumes of cortex and medulla were determined using stereological methods. The results were statistically analyzed and the periods of significant growth of these structures were marked. Results. Fetal kidney's cortex and medulla grew continually with a very high coefficient of linear correlation with crown-rump length. The cortex/medulla ratio was minimal in the first half of V lunar month, when medulla grew most rapidly and it was maximal immediately before birth, when cortex achieved its maximum. Conclusion. This study was an effort to provide some parameters which would help in the future investigations of the development of human fetal kidney.